Titanium dioxide-graphene composite material as well as preparation method and application thereof

The titanium dioxide-graphene composite material was prepared in one step by hydrothermal method, which solved the problems of low preparation efficiency and poor photocatalytic effect in the prior art, and achieved efficient preparation and excellent photocatalytic performance, so that it could effectively degrade under multi-spectral conditions. Pollutants.

CN119425656APending Publication Date: 2025-02-14CHINA FAW CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411327938.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing methods for composite titanium dioxide and graphene materials have problems of low preparation efficiency and poor photocatalytic effect.

Method used

The hydrothermal method is used to prepare graphene oxide and butyl titanate in one step. The titanium ions are better dispersed by non-ionic surfactants, which promotes the complete reduction of graphene oxide and the increase of titanium dioxide grains, thus forming a rutile type and Anatase crystal titanium dioxide-graphene composite material.

Benefits of technology

The preparation efficiency and photocatalytic performance of titanium dioxide-graphene composite materials are improved, so that it can effectively photocatalyze the degradation of pollutants such as rhodamine B under ultraviolet and visible light conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425656A_ABST
    Figure CN119425656A_ABST
Patent Text Reader

Abstract

The invention provides a titanium dioxide-graphene composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: dispersing a certain amount of graphene oxide in an organic solvent to obtain a graphene oxide solution; adding butyl titanate into the graphene oxide solution, and stirring and mixing to obtain a first mixed solution; uniformly mixing a certain amount of nonionic surfactant with water to obtain a second mixed solution; gradually adding the second mixed solution into the first mixed solution, and uniformly stirring to obtain a third mixed solution; and carrying out hydrothermal treatment on the third mixed solution at a predetermined temperature for a predetermined time, cooling, filtering and drying to obtain the titanium dioxide-graphene composite material. According to the method, the preparation efficiency is high, and the photocatalytic performance of the titanium dioxide-graphene composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a titanium dioxide-graphene composite material and a preparation method and application thereof. Background Art

[0002] Titanium dioxide has excellent properties such as small particle size, large specific surface area, and high relative density of interface atoms. It is widely used in photoelectric conversion functional materials, catalytic materials, biomedicine and other fields. However, titanium dioxide itself has certain limitations. On the one hand, titanium dioxide has a wide band gap and low utilization rate of visible light, and can only absorb the ultraviolet part of natural light; on the other hand, titanium dioxide has the problem of high quantum demand and easy recombination of photogenerated electrons and holes. The above two points are the main reasons for the limitation of titanium dioxide materials in practical applications. Graphene has a high theoretical specific surface area and excellent electron migration performance, and has a strong adsorption capacity for macromolecules. In order to enhance the photocatalytic redox activity of titanium dioxide, titanium dioxide is compounded with graphene materials to form a good electron transfer channel, avoid self-recombination of photogenerated electrons and photogenerated holes, expand the response range of the material to light, and enhance its photocatalytic performance. At present, there are many methods for compounding titanium dioxide and graphene materials, but they all have certain defects, resulting in problems such as low yield or poor photocatalytic effect. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a method for preparing a titanium dioxide-graphene composite material, which has a high preparation efficiency or a good photocatalytic effect of the prepared composite material.

[0004] In one aspect of the present invention, the present invention provides a method for preparing a titanium dioxide-graphene composite material. According to an embodiment of the present invention, the method for preparing a titanium dioxide-graphene composite material comprises: dispersing a certain amount of graphene oxide in an organic solvent to obtain a graphene oxide solution; adding butyl titanate to the graphene oxide solution, stirring and mixing to obtain a first mixed solution; mixing a certain amount of non-ionic surfactant with water to obtain a second mixed solution; gradually adding the second mixed solution to the first mixed solution, stirring to obtain a third mixed solution; hydrothermally treating the third mixed solution at a predetermined temperature for a predetermined time, cooling, filtering, and drying to obtain the titanium dioxide-graphene composite material. Therefore, in the preparation method, the hydrothermal method is used to prepare the titanium dioxide-graphene composite material from graphene oxide and butyl titanate in one step, thereby improving the preparation efficiency of the composite material; the non-ionic surfactant is used in the preparation method, which can better disperse the titanium ions in the entire solution system, promote the more thorough reduction of the graphene oxide, and at the same time is beneficial to the increase of the titanium dioxide grains and the enhancement of the photocatalytic performance of the titanium dioxide-graphene composite material; and, in the composite material prepared by the above method, the titanium dioxide crystal form includes not only the anatase type but also the rutile type, and the presence of the rutile type can make the photocatalytic performance of the titanium dioxide-graphene composite material more excellent.

[0005] According to an embodiment of the present invention, the ratio of the amount of the graphene oxide to the amount of the butyl titanate is (40-320) mg:10 mL. Preferably, the amount of the graphene oxide is 10-80 mg, and the amount of the butyl titanate is 2.5 mL.

[0006] According to an embodiment of the present invention, the ratio of the amount of the graphene oxide to the amount of the non-ionic surfactant is (10-80) mg: (1.5-3) g.

[0007] According to an embodiment of the present invention, the predetermined temperature is 120° C. to 180° C., and / or the predetermined time is 4 to 16 hours.

[0008] According to an embodiment of the present invention, the amount of graphene oxide used is 20 mg, the amount of butyl titanate used is 2.5 mL, the predetermined temperature is 160° C., and the predetermined time is 10 hours.

[0009] According to an embodiment of the present invention, the method for preparing the graphene oxide includes: adding sodium nitrate, concentrated sulfuric acid and graphite powder into a container, placing the container in an ice water bath, stirring, and obtaining a first mixture; adding potassium permanganate to the first mixture, and stirring in a first specific temperature water bath to obtain a second mixture; placing the second mixture in a second specific temperature water bath, and adding water and hydrogen peroxide to the second mixture to obtain a third mixture; washing the third mixture with hydrochloric acid to obtain a fourth mixture; centrifuging and drying the fourth mixture to obtain the graphene oxide, wherein the temperature of the first specific temperature water bath is 30 to 40° C., and the temperature of the second specific temperature water bath is 70 to 90° C.

[0010] In another aspect of the present invention, the present invention provides a titanium dioxide-graphene composite material. According to an embodiment of the present invention, the titanium dioxide-graphene composite material is prepared using the method described above. Thus, the preparation efficiency of the titanium dioxide-graphene composite material is high and the photocatalytic performance is excellent. Those skilled in the art will understand that the composite material has all the features and advantages of the method for preparing the titanium dioxide-graphene composite material described above, and no more details are given here.

[0011] According to an embodiment of the present invention, the light absorbed by the titanium dioxide-graphene composite material includes ultraviolet light and visible light.

[0012] According to an embodiment of the present invention, in the titanium dioxide-graphene composite material, the crystal form of titanium dioxide includes rutile type and anatase type.

[0013] According to an embodiment of the present invention, in the titanium dioxide-graphene composite material, the titanium dioxide is in the form of spherical particles with a particle size of 7 to 14 nm.

[0014] In another aspect of the present invention, the present invention provides a use of the above-mentioned titanium dioxide-graphene composite material in photocatalysis. Therefore, the titanium dioxide-graphene composite material has a relatively excellent photocatalytic effect.

[0015] According to an embodiment of the present invention, the titanium dioxide-graphene composite material can photocatalytically degrade rhodamine B, the usage ratio of the titanium dioxide-graphene composite material and the rhodamine B is (20-80) mg: (2-6) mg / L, and the light source is ultraviolet light, ultraviolet-visible light source or visible light. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0017] Figure 1is a flow chart of preparing a titanium dioxide-graphene composite material in one embodiment of the present invention;

[0018] Figure 2 is a flow chart of preparing graphene oxide in another embodiment of the present invention;

[0019] Figure 3 is a FE-SEM photograph of graphene oxide prepared in Example 1;

[0020] Figure 4 is a FEM photograph of graphene oxide prepared in Example 1;

[0021] Figure 5 is the XRD spectrum of graphene oxide prepared in Example 1;

[0022] Figure 6 is a FE-SEM photograph of the titanium dioxide-graphene composite material prepared in Example 1;

[0023] Figure 7 is a FM photo of the titanium dioxide-graphene composite material prepared in Example 1;

[0024] Figure 8 is the XRD spectrum of the titanium dioxide-graphene composite material prepared in Example 1;

[0025] Fig. 9 is the FT-IR spectrum of the titanium dioxide-graphene composite material prepared in Example 1;

[0026] Fig.10 is the XRD spectra of the titanium dioxide-graphene composite materials prepared in Examples 1 to 7;

[0027] Fig.11 is the UV-Vis spectra of the titanium dioxide-graphene composite materials prepared in Examples 1 to 7;

[0028] Fig.12 is a diagram showing the effect of photocatalytic degradation of Rhodamine B by the titanium dioxide-graphene composite material prepared in Examples 1 to 7;

[0029] Fig.13 is the XRD spectra of the titanium dioxide-graphene composite materials prepared in Example 1 and Example 8 to Example 13;

[0030] Fig.14 It is a diagram showing the effect of photocatalytic degradation of Rhodamine B by the titanium dioxide-graphene composite materials prepared in Examples 1 and 8 to 13;

[0031] Fig.15is the XRD spectra of the titanium dioxide-graphene composite materials prepared in Example 1 and Example 14 to Example 16;

[0032] Fig.16 It is a diagram showing the effect of photocatalytic degradation of Rhodamine B by the titanium dioxide-graphene composite materials prepared in Example 1 and Example 14 to Example 16;

[0033] Fig.17 It is a diagram showing the effect of photocatalytic degradation of Rhodamine B by the titanium dioxide-graphene composite materials prepared in Example 1 and Example 17 to Example 19;

[0034] Fig.18 It is a diagram showing the effect of photocatalytic degradation of Rhodamine B by the titanium dioxide-graphene composite materials prepared in Example 1 and Example 20 to Example 23;

[0035] Fig.19 This is a diagram showing the effect of photocatalytic degradation of Rhodamine B by the titanium dioxide-graphene composite material prepared in Example 1 and Example 24. DETAILED DESCRIPTION

[0036] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0037] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0038] In one aspect of the present invention, the present invention provides a method for preparing a titanium dioxide-graphene composite material. According to an embodiment of the present invention, referring to Figure 1 , the method for preparing the titanium dioxide-graphene composite material comprises:

[0039] S100: dispersing a certain amount of graphene oxide in an organic solvent to obtain a graphene oxide solution.

[0040] In some embodiments, the organic solvent in the above steps can be an organic solvent such as n-butanol or propanol, which can effectively dissolve graphene oxide. In some specific embodiments, after the graphene oxide and the organic solvent are evenly mixed, ultrasonic vibration is used until the graphene oxide is completely peeled off and two brown graphene oxide solutions are formed.

[0041] Furthermore, the concentration of the graphene oxide solution can be 0.5 to 2 mg / mL, such as 0.5 mg / mL, 0.8 mg / mL, 1.0 mg / mL, 1.2 mg / mL, 1.5 mg / mL, 1.8 mg / mL, 2.0 mg / mL, etc.

[0042] S200: adding butyl titanate to the graphene oxide solution, stirring and mixing to obtain a first mixed solution.

[0043] In some embodiments of the present invention, the ratio of the amount of graphene oxide to that of butyl titanate is (40-320) mg: 10 mL. Under the above ratio, graphene oxide and butyl titanate are fully compounded with titanium dioxide in the subsequent hydrothermal reaction. As the amount of graphene oxide increases, the photocatalytic performance of the composite material can be gradually improved. However, if the amount of graphene oxide is too much, it is easy to cause it to agglomerate, which in turn affects its photocatalytic effect. In some specific embodiments, the amount of graphene oxide is 10-80 mg, such as 10 mg, 20 mg, 30 mg, 40 mg, 50 mg, 60 mg, 70 mg, 80 mg, etc., and the amount of butyl titanate is 2.5 mL.

[0044] In some embodiments, the graphene oxide solution and butyl titanate can be mixed by magnetic stirring and ultrasonic vibration to obtain a fully mixed and uniform first mixed solution.

[0045] S300: uniformly mixing a certain amount of nonionic surfactant and water to obtain a second mixed solution.

[0046] In some specific embodiments, the above steps can also be mixed evenly by magnetic stirring to obtain the second mixed solution.

[0047] Further, the ratio of the amount of graphene oxide to the amount of nonionic surfactant is (10-80) mg: (1.5-3) g, for example, the amount of graphene oxide is 10 mg, 20 mg, 30 mg, 40 mg, 50 mg, 60 mg, 70 mg, 80 mg, etc., and the amount of nonionic surfactant is 1.5 g, 1.8 g, 2.0 g, 2.17 g, 2.5 g, 2.88 g, 3.0 g, etc. The above amount of nonionic surfactant can well disperse titanium ions in the entire solution system, promote the reduction of graphene oxide more thoroughly, and at the same time is conducive to the increase of titanium dioxide grains, enhance the photocatalytic performance of titanium dioxide-graphene composite materials, and will not avoid the waste or shortage of raw materials.

[0048] In some embodiments of the present invention, the non-ionic surfactant may be an OP emulsifier, such as Triton X-100. The above emulsifier can effectively achieve the above technical effects without causing side reactions with other ingredients such as graphene oxide and butyl titanate. At the same time, it is easy to remove in the subsequent post-treatment after the hydrothermal reaction.

[0049] S400: gradually adding the second mixed liquid into the first mixed liquid, stirring evenly, to obtain a third mixed liquid.

[0050] In the above steps, the second mixed solution can be slowly added to the first mixed solution and stirred until a uniform light gray solution, i.e., the third mixed solution, is obtained. This is conducive to the uniform dispersion of the non-ionic surfactant in the third mixed solution, which is conducive to its function, so that the titanium ions are dispersed in the entire solution system, thereby promoting the subsequent reduction of graphene oxide to be more thorough.

[0051] S500: subjecting the third mixed solution to hydrothermal treatment at a predetermined temperature for a predetermined time, cooling, filtering, and drying to obtain a titanium dioxide-graphene composite material.

[0052] In some embodiments of the present invention, the above steps can be performed in a polytetrafluoroethylene liner, specifically: the third mixed solution is transferred to the polytetrafluoroethylene liner, and then hydrothermally treated at a predetermined temperature for a predetermined time. After the reaction is completed, the mixture is cooled to room temperature in a natural environment, and then filtered, washed with water, dried, and other post-treatments are performed to obtain a titanium dioxide-graphene composite material.

[0053] According to some embodiments of the present invention, the predetermined temperature is 120°C to 180°C, such as 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc., and the predetermined time is 4 to 16 hours, such as 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, etc. Under the above reaction conditions, the hydrothermal reaction can be smoothly carried out and the reaction efficiency can be improved. Among them, if the reaction temperature is low, titanium dioxide particles are easily deposited on the surface of graphene, and a large number of titanium dioxide particles agglomerate together, reducing the specific surface area of ​​titanium dioxide-graphene composite materials, thereby reducing their photocatalytic effect; if the reaction temperature is high, the chemical bond between titanium dioxide and graphene is broken, which will also reduce the photocatalytic performance of the composite material. If the reaction time is short, graphene oxide is not completely reduced; if the reaction time is long, the chemical bonds between titanium dioxide and graphene are broken, affecting the photocatalytic effect of the composite material and its ability to transfer photogenerated electrons and holes.

[0054] In some specific embodiments, the predetermined temperature of the hydrothermal reaction is 160° C., and the predetermined reaction time is 10 hours. Under these conditions, the photocatalytic performance of the prepared composite material is optimal.

[0055] According to an embodiment of the present invention, the above method for preparing a titanium dioxide-graphene composite material has at least the following technical effects:

[0056] 1. The hydrothermal method is used to prepare titanium dioxide-graphene composite materials from graphene oxide and butyl titanate in one step, which improves the preparation efficiency of the composite materials. At the same time, the preparation method is simple, easy to operate, and environmentally friendly. Almost no by-products harmful to the environment are produced during the preparation process, and the recrystallization process in the hydrothermal synthesis makes the product have a higher purity;

[0057] 2. Directly using graphene oxide and butyl titanate as initial reactants avoids the redundant step of reducing graphene oxide to graphene for further reaction; at the same time, butyl titanate is adsorbed onto the surface of graphene oxide in n-butanol. As the solvent thermal reaction time increases, the surface active groups of graphene oxide decrease, and the reduction is more thorough. At the same time, the titanium dioxide grains tend to increase. The above advantages are conducive to enhancing the photocatalytic performance of titanium dioxide-graphene materials;

[0058] 3. The preparation method uses a non-ionic surfactant, which can better disperse titanium ions in the entire solution system, promote the reduction of graphene oxide more thoroughly, and at the same time is conducive to the increase of titanium dioxide grains and enhance the photocatalytic performance of titanium dioxide-graphene composite materials;

[0059] 4. The composite material prepared by the above method includes titanium dioxide crystal forms including not only anatase type but also rutile type. The presence of this crystal form can make the photocatalytic performance of the titanium dioxide-graphene composite material more excellent.

[0060] In some embodiments of the present invention, it can be found through testing that: the titanium dioxide in the titanium dioxide-graphene composite material prepared by the above method is spherical particles with a size of 7 to 14 nm, such as 7 nm, 8 nm, 10 nm, 12 nm, 14 nm, etc. The titanium dioxide grains are relatively large, which is beneficial to enhancing the photocatalytic performance of the titanium dioxide-graphene composite material; the titanium dioxide is relatively evenly dispersed on the surface of the graphene, most of which is anatase phase and a small part is rutile phase. The presence of rutile crystal form can make the photocatalytic performance of the titanium dioxide-graphene composite material more excellent; the light absorbed by the titanium dioxide-graphene composite material includes ultraviolet light and visible light, that is, the titanium dioxide-graphene composite material of the present invention can achieve photocatalysis under the conditions of ultraviolet light and / or visible light, which expands the light absorption wavelength of the titanium dioxide-graphene composite material, and further expands the application conditions and fields of the titanium dioxide-graphene composite material.

[0061] According to an embodiment of the present invention, referring to Figure 2 The raw material graphene oxide in the above preparation method can be prepared by the following method steps:

[0062] S110: Sodium nitrate, concentrated sulfuric acid and graphite powder are added into a container, and the container is placed in an ice water bath and stirred to obtain a first mixture.

[0063] In some specific embodiments, the operation steps of step S110 may be: putting sodium nitrate and concentrated sulfuric acid into a large beaker, adding graphite powder along the edge of the beaker, and stirring in an ice water bath (0-3° C.) to obtain a first mixture.

[0064] S120: adding potassium permanganate to the first mixture, and stirring in a water bath at a first specific temperature to obtain a second mixture.

[0065] In some specific embodiments, the operation steps of step S120 can be: slowly adding potassium permanganate to the first mixture within a specific time (such as 1 hour), and then stirring in a first specific temperature water bath to obtain a second mixture. The temperature of the first specific temperature water bath is 30-40°C, such as 30°C, 32°C, 35°C, 38°C, 40°C, etc.

[0066] S130: placing the second mixture in a water bath at a second specific temperature, and adding water and hydrogen peroxide to the second mixture to obtain a third mixture.

[0067] In some specific embodiments, the operation steps of step S130 can be: adding a certain amount of pure water to the second mixture, the rate of the separatory funnel when adding water is 1 to 3 drops / s (i.e., the dripping rate is 1 to 3 drops / s), keeping it warm in a second specific temperature water bath for a specific time after the dripping, and then adding a certain amount of pure water and a certain concentration of hydrogen peroxide again, standing and stratifying overnight to obtain a third mixture. Wherein, the temperature of the second specific temperature water bath is 70 to 90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C, etc.; the water bath insulation time is 15 to 45 minutes, such as 15 minutes, 30 minutes, 45 minutes, etc.; the amount of water dripped by the separatory funnel for the first time can be 180 to 220 ml, such as 200 ml; the amount of water added for the second time can be 180 to 220 ml, such as 200 ml.

[0068] S140: washing the third mixture with hydrochloric acid to obtain a fourth mixture.

[0069] In some specific embodiments, the operation steps of step S140 can be: washing with hydrochloric acid (adding 200 mL of pure water and then adding 30 mL of concentrated hydrochloric acid) 3 times, standing overnight after each washing, and then centrifuging and washing with water until neutral, to obtain a fourth mixture.

[0070] S150: centrifuging and drying the fourth mixture to obtain graphene oxide.

[0071] In some specific embodiments, the operation steps of step S150 can be: subject the fourth mixture to high-power ultrasound, then centrifuge at a certain speed, remove the supernatant after centrifugation, place the obtained sample on a surface dish, and dry to obtain graphene oxide. The centrifugal speed can be 3000-5000r / min, such as 3000r / min, 4000r / min, 5000r / min, etc.; the centrifugal treatment time is 5-10 minutes; the drying temperature can be 50-70°C, such as 50°C, 60°C, 70°C, etc.

[0072] According to an embodiment of the present invention, in the above-mentioned method for preparing graphene oxide, there is no special requirement for the amount of raw materials such as sodium nitrate, concentrated sulfuric acid, graphite powder, potassium permanganate, and hydrogen peroxide. Those skilled in the art can flexibly design it according to actual needs and reaction conditions, and no restriction is made here.

[0073] According to an embodiment of the present invention, the above-mentioned method steps for preparing graphene oxide can improve the defects of the original Hummers method for preparing graphene oxide, such as large amount of graphite, high reaction temperature, and insufficient oxidation; moreover, the above-mentioned gradient temperature heating method, graphite pretreatment (ice water bath), pre-oxidation (first specific temperature water bath 30-40°C), and oxidation (second specific temperature water bath 70-90°C), are safer and more fully reactive than the original Hummers method; in some embodiments, it can be found through testing that the graphene oxide prepared by the above-mentioned method of the present invention is in the form of a transparent thin layer with a thickness of about 1.2nm and a high degree of oxidation.

[0074] In another aspect of the present invention, the present invention provides a titanium dioxide-graphene composite material. According to an embodiment of the present invention, the titanium dioxide-graphene composite material is prepared using the method described above. Thus, the preparation efficiency of the titanium dioxide-graphene composite material is high and the photocatalytic performance is excellent. Those skilled in the art will understand that the composite material has all the features and advantages of the method for preparing the titanium dioxide-graphene composite material described above, and no more details are given here.

[0075] According to some embodiments of the present invention, the light absorbed by the titanium dioxide-graphene composite material includes ultraviolet light and visible light. That is, the titanium dioxide-graphene composite material of the present invention can achieve photocatalysis under the conditions of ultraviolet light and / or visible light, which expands the light absorption wavelength of the titanium dioxide-graphene composite material, and further expands the application conditions and fields of the titanium dioxide-graphene composite material.

[0076] According to some embodiments of the present invention, in the titanium dioxide-graphene composite material, the crystal form of titanium dioxide includes rutile and anatase. Therefore, the presence of the rutile crystal form can make the photocatalytic performance of the titanium dioxide-graphene composite material more excellent.

[0077] According to some embodiments of the present invention, in the titanium dioxide-graphene composite material, the titanium dioxide is a spherical particle with a particle size of 7 to 14 nm, such as 7 nm, 8 nm, 10 nm, 12 nm, 14 nm, etc. It can be seen that the titanium dioxide grains in the composite material of the present invention are relatively large, which is conducive to enhancing the photocatalytic performance of the titanium dioxide-graphene composite material.

[0078] In another aspect of the present invention, the present invention provides a use of the above-mentioned titanium dioxide-graphene composite material in photocatalysis. Therefore, the titanium dioxide-graphene composite material has a relatively excellent photocatalytic effect.

[0079] According to an embodiment of the present invention, the titanium dioxide-graphene composite material can photocatalytically degrade Rhodamine B, and the dosage ratio of the titanium dioxide-graphene composite material and Rhodamine B is (20-80) mg: (2-6) mg / L. For example, the dosage of the titanium dioxide-graphene composite material is 2 mg, 3 mg, 4 mg, 5 mg, 6 mg, 7 mg, 8 mg, etc., and the dosage of Rhodamine B is 2 mg / L, 3 mg / L, 4 mg / L, 5 mg / L, 6 mg / L, etc. The above-mentioned ratio can make the composite material fully photocatalytically degrade Rhodamine B. When the dosage of the catalyst titanium dioxide-graphene composite material is small, after the composite material and the Rhodamine B molecules in the solution reach adsorption-desorption equilibrium, titanium dioxide does not fully utilize photons, resulting in the hydroxyl radicals (·OH) and superoxide radicals (·O2 - ) is reduced, and the degree of free radical reaction with Rhodamine B molecules is limited, which reduces the photocatalytic performance of the composite material; when the amount of catalyst titanium dioxide-graphene composite material is large, there is still a large amount of composite material suspended in the solution, which affects the effective utilization of photons by the composite material and the effective photodegradation of Rhodamine B molecules.

[0080] In some embodiments, the light source for photocatalysis is ultraviolet light, ultraviolet-visible light source or visible light. Among them, the ultraviolet light source can be specifically a 450W self-ballasted fluorescent high-pressure mercury lamp, and the ultraviolet-visible light source can be specifically a PerfectLight PLS-SXE300 xenon lamp. It can be seen that after titanium dioxide and graphene are combined, the photogenerated hole-electron transfer rate of the semiconductor catalyst is improved, the wavelength range of titanium dioxide's original absorption of natural light sources is expanded, the photon utilization rate of titanium dioxide is improved, and the photocatalytic performance of the titanium dioxide-graphene composite material is improved.

[0081] In some embodiments of the present invention, the specific steps of photocatalytic degradation of Rhodamine B using titanium dioxide-graphene composite materials can be: measuring a certain volume of Rhodamine B solution with an initial reaction concentration of 2 to 6 mg / L, adding a certain mass of titanium dioxide-graphene composite materials, and performing a photodegradation experiment in a closed light-shielded environment using a 450W self-ballasted fluorescent high-pressure mercury lamp or a PerfectLight PLS-SXE300 xenon lamp as a light source. Magnetic stirring is performed for 1 hour in a closed light-shielded environment so that the titanium dioxide-graphene composite material reaches an adsorption-desorption equilibrium state. Sampling, centrifugation, and absorbance measurement are performed at intervals of 30 minutes. A visible spectrophotometer is used to quantitatively analyze the content of the Rhodamine B solution after photodegradation of the titanium dioxide-graphene composite material, and the content of the Rhodamine B solution is expressed by the decolorization rate D. The present invention can use a 722s visible spectrophotometer with a spectrum width of 6nm to measure the absorbance within a wavelength of λ=330nm~1000nm. The λ of Rhodamine B maxThe calculation formula of decolorization rate D is as follows: D = [(A0-A) / A0] × 100%, where: D-decolorization rate (%); A0-absorbance of the sample before irradiation (L / g·cm); A-absorbance of the sample when the irradiation time is t (L / g·cm).

[0082] Example

[0083] Example 1

[0084] Preparation method of graphene oxide: first, put 1.5g sodium nitrate and 50mL concentrated sulfuric acid into a large beaker, then add graphite powder along the edge of the beaker, and stir in an ice water bath (0-3°C) to obtain a first mixture. Slowly add 8g potassium permanganate to the first mixture within 1 hour for oxidation, and then stir in a 35°C water bath for 6 hours to obtain a second mixture. Add 200 mL of pure water to the second mixture at a rate of 1 to 3 drops / s in the separatory funnel. After the dropwise addition, keep warm in a water bath at 80°C for 30 min, then add 200 mL of pure water and 20 mL of 30% hydrogen peroxide to obtain a third mixture, and let stand for stratification overnight; wash with hydrochloric acid (add 200 mL of pure water, then add 30 mL of concentrated hydrochloric acid) 3 times, let stand overnight after each washing, then centrifuge and wash with water until neutral to obtain a fourth mixture; use high-power ultrasound for 0.5 h on the fourth mixture, then centrifuge at 4000 r / min for 8 min, remove the supernatant after centrifugation, place the obtained sample on a watch glass, and then dry it at 60°C for a period of time to obtain graphene oxide.

[0085] Preparation method of titanium dioxide-graphene composite material: weigh 30 mg of the prepared graphene oxide, add 30 mL of n-butanol, mix evenly, and then ultrasonically vibrate for 1 hour until it is completely peeled off and a bright yellow-brown graphene oxide solution is formed, then measure 2.5 mL of butyl titanate, magnetically stir for 30 minutes, and ultrasonically vibrate for 30 minutes to obtain a first mixed solution; measure 2.17 g of Triton X-100 and 45 mL of deionized water, mix evenly, and then magnetically stir for 30 minutes to obtain a uniform solution, which is the second mixed solution; slowly drip the second mixed solution into the first mixed solution, and magnetically stir for 30 minutes until a uniform bright gray solution is prepared, which is the third mixed solution; finally, transfer the bright gray third mixed solution into a 100 mL polytetrafluoroethylene liner, hydrothermally treat it at 160° C. for 10 hours, cool it to room temperature under a natural environment, and then filter it, wash it with water, and dry it at 60° C. to obtain a titanium dioxide-graphene composite material.

[0086] Photocatalytic performance test of titanium dioxide-graphene composite material: 150mL of Rhodamine B solution with an initial reaction concentration of 4mg / L was measured, and 0.04g of titanium dioxide-graphene composite material was added. The photodegradation experiment was carried out in a closed light-shielding environment using a 450W self-ballasted fluorescent high-pressure mercury lamp. Magnetic stirring was performed for 1h in a closed light-shielding environment to allow the composite material to reach an adsorption-desorption equilibrium state. Sampling, centrifugation, and absorbance measurement were performed at intervals of 30min. The content of the Rhodamine B solution after photodegradation of the titanium dioxide-graphene composite material was quantitatively analyzed using a visible spectrophotometer, and the content of the Rhodamine B solution was expressed as the decolorization rate D.

[0087] Example 2 to Example 16

[0088] The difference between Examples 2 to 16 and Example 1 is that the amount of graphene oxide, the reaction temperature of the hydrothermal treatment, and the reaction time of the hydrothermal treatment are changed. For details, please refer to Table 1.

[0089] Table 1

[0090] Graphene oxide dosage / mg Reaction time / h Reaction temperature / ℃ Example 1 30 10 160 Example 2 10 10 160 Example 3 20 10 160 Example 4 40 10 160 Example 5 50 10 160 Example 6 60 10 160 Example 7 80 10 160 Example 8 30 4 160 Example 9 30 6 160 Example 10 30 8 160 Embodiment 11 30 12 160 Example 12 30 14 160 Example 13 30 16 160 Embodiment 14 30 10 120 Embodiment 15 30 10 140 Example 16 30 10 180

[0091] Example 17 to Example 23

[0092] The difference between Examples 17 to 23 and Example 1 is that in the photocatalytic test, the amount of titanium dioxide-graphene composite material, the initial concentration of rhodamine B and the type of light source can be seen in Table 2.

[0093] Table 2

[0094]

[0095]

[0096] Test Characterization:

[0097] The graphene oxide prepared in Example 1 was scanned by electron microscope to obtain the following Figure 3 The FE-SEM (field emission scanning electron microscope) photo shown is from Figure 3 It can be seen that the surface of the prepared graphene oxide has obvious wrinkles and the edges are curled. The graphite raw material is a compact and ordered layered structure. After being strongly oxidized by concentrated sulfuric acid and potassium permanganate, the original layered structure of the graphite will be destroyed and the distance between the graphite layers will increase, indicating that the prepared graphene oxide has a high degree of oxidation.

[0098] The graphene oxide prepared in Example 1 was scanned by electron microscope to obtain the following Figure 4 The FEM (transmission electron microscope) photo shown is from Figure 4It can be seen that the prepared graphene oxide is in the form of a transparent thin layer, but some of the graphene oxide has multi-layer stacking and wrinkles, which makes the sample size different and presents different transparencies. There are black spots in some parts of the sample, which is caused by the solvent not being completely dried during the sample preparation process. The prepared sample is basically a single layer of graphene oxide. The wrinkles and stacking on the sample surface reduce the surface free energy of the two-dimensional carbon skeleton in the graphene oxide. It can be seen that this is consistent with its FE-SEM characterization results.

[0099] The graphene oxide prepared in Example 1 was subjected to XRD spectrum analysis to obtain the following Figure 5 The XRD spectrum shown by Figure 5 It can be seen that the prepared graphene oxide presents a characteristic diffraction peak at a diffraction angle 2θ of 11.064°, corresponding to the (001) crystal plane of graphene oxide, and the interplanar spacing d is 7.9891nm. According to the Debye-Scherrer formula: Dhkl = kλ / βcosθ, where k (Scherrer constant) is 0.89, λ (ray source wavelength) is 0.15418nm, and β (half-peak width of the diffraction peak) is 0.546rad, the grain diameter of graphene oxide perpendicular to the crystal plane (001) is calculated to be 0.2525nm. After graphite is oxidized by strong oxidants such as concentrated sulfuric acid and potassium permanganate, a new crystalline structure is formed. It can be seen that strong oxidants such as concentrated sulfuric acid and potassium permanganate oxidize the graphite raw material, increase the graphite interlayer spacing, and allow oxygen-containing functional groups to be inserted into the carbon plane gap of the original graphite.

[0100] The titanium dioxide-graphene composite material prepared in Example 1 was scanned by electron microscope to obtain the following Figure 6 The FE-SEM (field emission scanning electron microscope) photo shown is from Figure 6 It can be seen that in the composite material, the morphology of titanium dioxide is spherical particles with a size of about 10 nm, and the titanium dioxide particles are relatively evenly dispersed on the surface of the graphene material.

[0101] The titanium dioxide-graphene composite material prepared in Example 1 was subjected to ultrasonic vibration for 6 hours and then scanned by electron microscope to obtain the following Figure 7 The FEM (transmission electron microscope) photo shown is from Figure 7 It can be seen that titanium dioxide in the composite material is a spherical particle with a size of about 10nm. After a long period of ultrasonic vibration, titanium dioxide does not fall off the surface of graphene and is still evenly loaded on the surface of the graphene material. In addition, a small amount of graphene still agglomerates.

[0102] The titanium dioxide-graphene composite material prepared in Example 1 was subjected to XRD spectrum analysis to obtain the following Figure 8 The XRD spectrum shown by Figure 8 It can be seen that the XRD spectrum shows mixed crystal titanium dioxide, including anatase titanium dioxide and rutile titanium dioxide. The sample shows obvious characteristic diffraction peaks at diffraction angles 2θ of 25.355°, 38.643°, 48.143°, 53.973°, 55.184°, 62.810°, 70.456° and 75.200°. The characteristic diffraction peaks at diffraction angles 2θ of 25.355°, 38.643°, 48.143°, 53.973°, 62.810°, 70.456° and 75.200° correspond to the (101) crystal plane, (112) crystal plane, (200) crystal plane, (105) crystal plane, (204) crystal plane, (220) crystal plane and (215) crystal plane of anatase titanium dioxide. Compared with the standard card PDF#65-5714, it is shown that the prepared sample contains typical anatase titanium dioxide; the characteristic diffraction peak at a diffraction angle 2θ of 55.184° corresponds to the (211) crystal plane of rutile titanium dioxide, and compared with the standard card PDF#21-1276, it is shown that the prepared composite material contains rutile titanium dioxide.

[0103] The titanium dioxide-graphene composite material prepared in Example 1 was subjected to infrared spectrum analysis to obtain the following Fig. 9 The FT-IR spectrum shown is Fig. 9 It can be seen that the prepared titanium dioxide-graphene composite material has a wave number of 3424 cm -1 The absorption peak at 2929 cm-1 is attributed to the stretching vibration of hydroxyl (-OH) in water. -1 2850cm -1 The absorption peak at 1618 cm-1 is attributed to the stretching vibration of methyl (-CH3) and methylene (-CH2). -1 There is a strong vibration absorption peak at 1743cm -1 The absorption peak at 1402 cm-1, which is attributed to the stretching vibration of the carbonyl C=O bond in the carboxyl group (-COOH), disappears. -1 The absorption peak at the wave number 1071cm -1 The absorption peak attributable to the stretching vibration of the COC bond in the alkoxy group is also significantly weakened. -1 The results show that the graphene oxide is almost completely reduced.

[0104] The XRD spectra of the titanium dioxide-graphene composite materials in Examples 1 to 7 (the variable is the amount of graphene oxide) are tested respectively, as shown in FIG. Fig.10 As shown by Fig.10It can be seen that the XRD spectrum shows mixed crystal titanium dioxide, including anatase and rutile. The prepared composite material shows obvious crystal characteristic diffraction peaks at diffraction angles 2θ of 25.367°, 38.066°, 48.157°, 54.050°, 55.202°, ​​62.865°, 70.477° and 75.275°. The characteristic diffraction peaks at diffraction angles 2θ of 25.367°, 38.066°, 48.157°, 54.050°, 62.865°, 70.477° and 75.275° correspond to the (101) crystal plane, (112) crystal plane, (200) crystal plane, (105) crystal plane, (204) crystal plane, (220) crystal plane and (215) crystal plane of anatase type. Compared with the standard card PDF#65-5714, it is shown that the prepared composite material contains anatase type; the characteristic diffraction peak at a diffraction angle 2θ of 55.202° corresponds to the (211) crystal plane of rutile type, and compared with the standard card PDF#21-1276, it is shown that the prepared composite material contains rutile type. The characteristic peak of graphene oxide at 11.064° disappears, and the graphene diffraction peak is located at 24.5°, which is covered by the strong diffraction peak of anatase titanium dioxide (101) crystal plane at 25.367°.

[0105] The UV-Vis spectra of the titanium dioxide-graphene composite materials in Examples 1 to 7 (the variable is the amount of graphene oxide) are tested respectively, as shown in FIG. Fig.11 As shown, the light response range of the titanium dioxide-graphene composite material can be observed. At 400nm, all titanium dioxide-graphene composite materials with different graphene oxide dosages show a basic background absorption peak. Compared with pure titanium dioxide, due to the increase in solvent polarity, the excited state energy will decrease more compared to the ground state, and the background absorption peak of the titanium dioxide-graphene composite material will be red-shifted. The composite of graphene causes the photocatalyst composite material to induce a continuous background absorption band in the range of 400-600nm, and the background absorption wavelength range will be expanded. Therefore, it is difficult to determine the red-shift value. As the amount of graphene oxide decreases, the background absorption peak intensity in the range of 400-600nm gradually increases, gradually tending to the background absorption peak of pure titanium dioxide.

[0106] The titanium dioxide-graphene composite materials in Examples 1 to 7 (the variable is the amount of graphene oxide) were respectively used to photocatalytically degrade rhodamine B. The catalytic effects are as follows: Fig.12As shown, under ultraviolet light conditions, as the photocatalytic reaction proceeds, the decolorization rate D (ordinate) of the Rhodamine B solution shows an increasing trend until it levels off. When the photodegradation reaction time reaches 3h, the decolorization rate of most composite materials for the Rhodamine B solution reaches more than 85%. When the amount of graphene oxide is 10mg and 20mg, the decolorization rate of the Rhodamine B solution reaches 100% when the photodegradation reaction time reaches 2.5h; among them, compared with the composite material with 60mg of graphene oxide, the decolorization rate of the Rhodamine B solution increases when the amount of graphene oxide is 80mg. At this time, the strong adsorption of graphene is the main influencing factor of the change in decolorization rate. In summary, as the amount of graphene oxide increases, the decolorization rate of the Rhodamine B solution shows a trend of first decreasing and then increasing. The reason is that when the amount of graphene oxide is small, titanium dioxide is effectively embedded in the graphene surface, thereby improving the photocatalytic performance of the composite material; when the amount of graphene oxide is large, graphene agglomerates, resulting in a decrease in its photocatalytic performance.

[0107] The XRD spectra of the titanium dioxide-graphene composite materials in Example 1, Example 8 to Example 13 (the variable is the reaction time) are tested respectively. Fig.13 As shown in the figure, the spectrum is mixed crystal titanium dioxide, including anatase and rutile. The obtained product shows obvious crystal characteristic diffraction peaks at diffraction angles 2θ of 25.355°, 38.643°, 48.143°, 53.973°, 55.184°, 62.810°, 70.456° and 75.200°. Among them, the characteristic diffraction peaks at diffraction angles 2θ of 25.355°, 38.643°, 48.143°, 53.973°, 62.810°, 70.456° and 75.200° correspond to the (101) crystal plane, (112) crystal plane, (200) crystal plane, (105) crystal plane, (204) crystal plane, (220) crystal plane and (215) crystal plane of anatase titanium dioxide. Compared with the standard card PDF#65-5714, it is shown that the prepared composite material contains typical anatase titanium dioxide; the characteristic diffraction peak at a diffraction angle 2θ of 55.184° corresponds to the (211) crystal plane of rutile titanium dioxide, and compared with the standard card PDF#21-1276, it is shown that the prepared composite material contains rutile. By comparison, it can be found that the relative peak value is the highest when the reaction time is 10h.

[0108] The titanium dioxide-graphene composite materials in Examples 1, 8 to 13 (the variable is the reaction time) were respectively used to photocatalytically degrade rhodamine B. The catalytic effects are as follows: Fig.14As shown in the figure, under ultraviolet light conditions, as the reaction time continues to increase, the decolorization rate of the Rhodamine B solution shows a trend of first increasing and then decreasing. When the reaction time is 10h, the photocatalytic effect is stable, and the decolorization rate of the Rhodamine B solution can reach 100%. The reason is that when the reaction time is short, the graphene oxide is not completely reduced; when the reaction time is long, the chemical bond between titanium dioxide and graphene is broken, which affects the composite material's adsorption capacity for Rhodamine B and its ability to transfer photogenerated electrons-holes. When the reaction time is 10h, the graphene oxide can be completely reduced, and there will not be too many titanium dioxide particles deposited on the graphene surface. This is consistent with the conclusion that the relative peak in the composite material with a reaction time of 10h in the XRD spectrum is the highest.

[0109] The XRD spectra of the titanium dioxide-graphene composite material in Example 1, Example 14 to Example 16 (the variable is the reaction temperature) are respectively adopted, as shown in Fig.15 As shown in the figure, the spectrum is mixed crystal titanium dioxide, including anatase titanium dioxide and rutile titanium dioxide. The prepared composite material shows obvious characteristic diffraction peaks at diffraction angles 2θ of 25.308°, 38.571°, 48.046°, 53.884°, 55.071°, 62.690°, 70.301° and 75.051°. The characteristic diffraction peaks at diffraction angles 2θ of 25.308°, 38.571°, 48.046°, 53.884°, 62.690°, 70.301° and 75.051° correspond to the (101) crystal plane, (112) crystal plane, (200) crystal plane, (105) crystal plane, (204) crystal plane, (220) crystal plane and (215) crystal plane of anatase TiO2. Compared with the standard card PDF#65-5714, it is shown that the prepared composite material contains typical anatase titanium dioxide; the characteristic diffraction peak at a diffraction angle 2θ of 55.071° corresponds to the (211) crystal plane of rutile titanium dioxide, and compared with the standard card PDF#21-1276, it is shown that the prepared composite material contains rutile titanium dioxide. By comparison, it can be found that when the reaction temperature is 160°C, the relative peak value is the highest.

[0110] The titanium dioxide-graphene composite materials in Examples 1, 14 to 16 (the variable is the reaction temperature) were respectively used to photocatalytically degrade rhodamine B. The catalytic effects are as follows: Fig.16As shown in the figure, with the continuous increase of the photodegradation reaction time, the decolorization rate of the Rhodamine B solution shows an increasing trend. Among them, when the reaction temperature is 160℃ and the photodegradation reaction time reaches 2.5h, the decolorization rate of the Rhodamine B solution can reach 89.6%, and the photodegradation effect of Rhodamine B is the best. It can be inferred that when the reaction temperature is 160℃, it is suitable for titanium dioxide to be loaded on the surface of graphene, and it has relatively excellent photocatalytic performance. When the reaction temperature is low, titanium dioxide particles are easily deposited on the surface of graphene, and a large number of titanium dioxide particles agglomerate together, reducing the specific surface area of ​​the titanium dioxide-graphene composite material; when the reaction temperature is high, the chemical bond between titanium dioxide and graphene is broken, which reduces the photocatalytic performance of the composite material.

[0111] The titanium dioxide-graphene composite materials in Example 1, Example 17 to Example 19 and Comparative Example 1 (the variable is the amount of the composite material in the photocatalytic reaction) were used to photocatalytically degrade rhodamine B. The catalytic effects are as follows: Fig.17 As shown in the figure, when the catalyst dosage is 0.04g and the photodegradation reaction time is 2.5h, the decolorization rate of Rhodamine B solution can reach 97.4%, and the photodegradation effect of Rhodamine B is the best; while when the catalyst dosage is 0.02g, 0.06g and 0.08g, and the photodegradation reaction time is 2.5h, the decolorization rate of Rhodamine B solution is less than 70%. The reason is that when the catalyst dosage is small, after the composite material and the Rhodamine B molecules in the solution reach adsorption-desorption equilibrium, titanium dioxide does not make sufficient use of photons, resulting in the hydroxyl radicals (·OH) and superoxide radicals (·O2 - ) is reduced, and the degree of free radical reaction with rhodamine B molecules is limited, which reduces the photocatalytic performance of the composite material; when the amount of catalyst is large, there is still a large amount of composite material suspended in the solution, which affects the effective use of photons by the composite material and the effective photodegradation of rhodamine B molecules. From the above comparison, it can be seen that for a rhodamine solution with a concentration of 4 mg / L, a catalyst dosage of 0.04 g is more appropriate.

[0112] The titanium dioxide-graphene composite materials in Examples 1, 20 to 23 (the variable is the initial concentration of rhodamine B in the photocatalytic reaction) were used to photocatalytically degrade rhodamine B. The catalytic effects are as follows: Fig.18As shown, with the increase of photodegradation reaction time, the decolorization rate of Rhodamine B solution shows a trend of increasing until saturation. When the concentration of Rhodamine B solution is 2mg / L and 3mg / L, after the photodegradation reaction time reaches 2.5h, the decolorization rate of Rhodamine B solution can reach 100%; in comparison, when the concentration of Rhodamine is 5mg / L and 6mg / L, the degradation effect of Rhodamine B is not particularly ideal. When the concentration of Rhodamine B solution is low, although the photocatalytic degradation effect is better, the absorbance value of the initial concentration of Rhodamine B is low, and there is not enough absorbance change threshold during the photocatalytic reaction; when the concentration of Rhodamine B solution is high, after the composite material reaches adsorption-desorption equilibrium, most of the Rhodamine B molecules still do not enter the catalyst gap, which reduces the photocatalytic performance of the composite material. In the above embodiment, 4mg / L is the best initial reaction concentration of Rhodamine B.

[0113] The titanium dioxide-graphene composite materials in Example 1 and Example 24 (the variable is the light source in the photocatalytic reaction) were used to photocatalytically degrade rhodamine B. The catalytic effects are as follows: Fig.19 As shown in the figure, with the increase of photodegradation reaction time, the decolorization rate of Rhodamine B solution shows a trend of increasing until saturation. Under ultraviolet light (UV) conditions, when the photodegradation reaction time reaches 2.5h, the decolorization rate of Rhodamine B solution reaches 97.4%; under ultraviolet-visible light (UV-Vis) conditions, when the photodegradation reaction time reaches 2.5h, the decolorization rate of Rhodamine B solution can reach 98.9%, and when the photodegradation reaction time reaches 3h, the decolorization rate of Rhodamine B solution is close to 100%. It can be seen that after titanium dioxide and graphene are combined, the photogenerated hole-electron transfer rate of the semiconductor catalyst is improved, the wavelength range of titanium dioxide's original absorption of natural light sources is expanded, and the photon utilization rate of titanium dioxide is improved, so that the composite material has excellent photocatalytic performance.

[0114] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0115] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0116] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a titanium dioxide-graphene composite material, characterized in that: include: dissolving a certain amount of graphene oxide in an organic solvent to obtain a graphene oxide solution; Adding butyl titanate to the graphene oxide solution, stirring and mixing to obtain a first mixed solution; Evenly mixing a certain amount of nonionic surfactant with water to obtain a second mixed solution; gradually adding the second mixed solution into the first mixed solution and stirring evenly to obtain a third mixed solution; The third mixed liquid is hydrothermally treated at a predetermined temperature for a predetermined time, cooled, filtered and dried to obtain the titanium dioxide-graphene composite material.

2. The method according to claim 1, characterized in that The ratio of the amount of graphene oxide to the amount of butyl titanate is (40-320) mg:10 mL. Preferably, the amount of graphene oxide used is 10-80 mg, and the amount of butyl titanate used is 2.5 mL.

3. The method according to claim 1, characterized in that The ratio of the amount of the graphene oxide to the amount of the non-ionic surfactant is (10-80) mg: (1.5-3) g.

4. The method according to claim 1, characterized in that: The predetermined temperature is 120° C. to 180° C., and / or the predetermined time is 4 to 16 hours.

5. The method according to any one of claims 1 to 4, characterized in that: The amount of graphene oxide used is 20 mg, the amount of butyl titanate used is 2.5 mL, the predetermined temperature is 160° C., and the predetermined time is 10 hours.

6. The method according to any one of claims 1 to 4, characterized in that: The method for preparing the graphene oxide comprises: Adding sodium nitrate, concentrated sulfuric acid and graphite powder into a container, and placing the container in an ice water bath, stirring, to obtain a first mixture; adding potassium permanganate to the first mixture, and stirring in a water bath at a first specific temperature to obtain a second mixture; placing the second mixture in a water bath at a second specific temperature, and adding water and hydrogen peroxide to the second mixture to obtain a third mixture; washing the third mixture with hydrochloric acid to obtain a fourth mixture; The fourth mixture is centrifuged and dried to obtain the graphene oxide, Wherein, the temperature of the first specific temperature water bath is 30-40°C, and the temperature of the second specific temperature water bath is 70-90°C.

7. A titanium dioxide-graphene composite material, characterized in that: The invention is prepared by the method according to any one of claims 1 to 6.

8. The titanium dioxide-graphene composite material according to claim 7, characterized in that: The titanium dioxide-graphene composite material absorbs light including ultraviolet light and visible light.

9. The titanium dioxide-graphene composite material according to claim 7, characterized in that: In the titanium dioxide-graphene composite material, the crystal forms of titanium dioxide include rutile and anatase.

10. The titanium dioxide-graphene composite material according to claim 7, characterized in that: In the titanium dioxide-graphene composite material, the titanium dioxide is in the form of spherical particles with a particle size of 7 to 14 nm.

11. Use of the titanium dioxide-graphene composite material according to any one of claims 7 to 10 in photocatalysis.

12. The use according to claim 11, characterized in that The titanium dioxide-graphene composite material can photocatalytically degrade rhodamine B. The usage ratio of the titanium dioxide-graphene composite material and the rhodamine B is (20-80) mg: (2-6) mg / L. The light source is ultraviolet light, ultraviolet-visible light source or visible light.

Citation Information

Patent Citations

  • Preparation method of graphene / titanium dioxide composite photocatalyst

    CN101890344A

  • Hydrothermal method for preparing graphene supported titanium dioxide

    CN106423129A

  • Method for uniformly loading nano titanium dioxide on surface of graphene oxide and photocatalyst

    CN117816145A